The Economy and Colonial Foreign Trade of Venezuela Before the Independence (2023)
The object of this article is to present, from a comparative historical perspective, some features of the Venezuelan export sector in the colony, particularly from the final part of this period, considering the effects of this activity on the economic, social and political structure, as a preamble of the independence process. The central hypothesis to be demonstrated is that the economic and commercial development that occurred in the second half of the 18th century created discrepancies between the productive and commercial elite. These contradictions became more acute at the end of the colonial period when other traditionally marginalized social groups joined the fray and when the Spanish colonial authorities and the metropolis itself became more interested in the region. The political economy of this process ¾conflict over the distribution of the economic surplus derived from foreign trade¾ became an additional ingredient of the independence process.